MOTIVASI BELAJAR SISWI KELAS VIII PADA PEMBELAJARAN BOLA BASKET DI SMP - Viyanti Kusuma Wardany, Dwi Mitra; Purnomo, Edi; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is based on female student who tend to be passive in following physical education, especially on basketball game. The object of this research is VIII grade female students at SMPN 1 Sungai Raya. This research aims to determine the motivationÂ to follow the basketball game of VIII grade female students SMPN 1 Sungai Raya. This research is quantitative descriptive. The method used is survey method. The population of this research is all VIII grade female students SMPN 1 Sungai Raya who numbered 212 studendts. The sample of this research is the VIII grade female students, The sampling technique used is random sampling Of these technique obtained as many as 68 female students. The instrument used is a questionnaire. The technique of analysis is to change the frequency into percentage form. The result of this research indicate that the motivation of VIII grade female students to follow the basketball game is low. It is based on the most frequency in the low category as many as 23 students or 32.82%. Motivation to follow the basketball game with very high category as many as 6 students or 5.88%, high as many as 22 students or 32.35%, medium as many as 16 students or 23.53%, low as many as 23 students or 33.82% and very low as many as 3 students or 4.41%.Â Keywords:Â Motivation, learning, basket ball, survey